Análisis de susceptibilidad a fluoroquinolonas de arcobacter aislados a partir de quesos frescos, obtenidos de los mercados municipales de Guaranda. - Goyes Guerra, Luis Israel (2020)
In this research the susceptibility to Fluoroquinolones of Arcobacter spp isolated from fresh cheeses, obtained from the municipal markets of Guaranda, was analyzed, so we considered; isolate microorganisms of the genus Arcobacter from consumer cheeses from the main markets of the City of Guaranda, identify colonies of the genus Arcobacter through biochemical and microscopic techniques, extract DNA from isolates morphologically and biochemically confirmed to belong to the genus of interest, amplify DNA obtained by PCR (polymerase chain reaction), finally analysis of the antimicrobiotic activity of Levofloxacin and Ciprofloxacin on the strains studied. In the present investigation, the type of analysis used was a descriptive statistical model where tests of analysis of means, percentages and frequencies were studied, all this in correspondence to the factors that were studied, which were 100 samples of cheeses from the main markets in the city of Guaranda, after a period of selective growth, Arcobacter strains were isolated from 66 of the 47 cheese samples analyzed, resulting in 25 strains obtained from the samples from the Bellavista market; While 41 strains were obtained from the November 10 Market, their DNA was extracted, the susceptibility to Fluoroquinolones and the genus Arcobacter isolated from fresh cheeses obtained in the municipal markets of Guaranda was analyzed, where 2/26 cases were be resistant to the bacteria, making up 7.69%; 19/26 cases showed intermediate resistance to Arcobacter, being 73.08%; finally 5/26 cases turned out to be susceptible, forming the remaining 19.23%.